Sustainable silvopastoral systems: theory and a practical case - Cañón, Jorge Federico Useche (2015)
Many changes are expected because of the climate change, especially from the agricultural activities done in the tropics. This thesis focuses on two aspects. The first one is to gather knowledge of environmentally sustainable silvopastoral systems; this view establishes the importance of tropical soils and their proper management in line with environmental and sustainable standards. The second part of the thesis is the application of these principles in a specific case: the 'El Paraíso' Farm improvement. The central objective or problem to solve of the thesis is to explain silvopastoril principles; and based on that to propose a project to improve meat production activities and at the same time help to preserve and to improve the environment. The methodology used in the thesis was to search and to analyze information on the subject, after that experimental and field research was conducted to raise the project that would combine the two parts of the work. At the end with the information gathered a project proposal was done. The objective was to propose the transformation of the production processes in the selected farm. After developing and presenting the project, the chances of project implementation were analyzed. The conclusion of the study was to present and discuss three possible scenarios after the implementation, it is discussed and expected that the positive scenario is reached. Finally the general conclusion presents the achievements, the opportunities and possible future expansions of the project.